2013
DOI: 10.1017/s0958344012000328
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of automatization through vocabulary learning using CALL: Can prompt language processing lead to better comprehension in L2 reading?

Abstract: Our study aims to optimize a multimedia application for vocabulary learning for English as a Foreign Language (EFL). Our study is based on the concept that difficulty in reading a text in a second language is due to the need for more working memory for word decoding skills, although the working memory must also be used for text comprehension skills. This implies that the automatization of word decoding to free the working memory is indispensable. Therefore, developing a multimedia application for vocabulary le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 25 publications
(27 reference statements)
2
10
0
4
Order By: Relevance
“…This study, therefore, hypothesizes that successful mobile-assisted L2 vocabulary learning through the technologically advanced representation of knowledge would enhance learner autonomy, as well as the automatization of vocabulary recall. Based on this hypothesis, this study verifies the effectiveness of MALL in a setting that differs from the one described in Sato et al (2013), focusing on phrases for academic writing. While developing mobile-based material to learn the phrases that are required to write an academic essay consisting of several paragraphs, empirical research was conducted to examine the following two research questions:…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…This study, therefore, hypothesizes that successful mobile-assisted L2 vocabulary learning through the technologically advanced representation of knowledge would enhance learner autonomy, as well as the automatization of vocabulary recall. Based on this hypothesis, this study verifies the effectiveness of MALL in a setting that differs from the one described in Sato et al (2013), focusing on phrases for academic writing. While developing mobile-based material to learn the phrases that are required to write an academic essay consisting of several paragraphs, empirical research was conducted to examine the following two research questions:…”
Section: Introductionsupporting
confidence: 64%
“…A previous study (Sato, Matsunuma, & Suzuki, 2013) revealed that using mobile devices to learn L2 vocabulary could enhance the automatization of vocabulary recall, which can save on cognitive resources, allowing them to be reapplied toward reading activities and thus successful L2 reading comprehension. Those findings supported the assertion of the efficacy of L2 learning using multimodal functions, like many other previous studies that argue that the convergence of technologies in learning resources will improve L2 learners' performance (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Other researchers have focused on the application of corpora for language acquisition in the classroom, showing varying degrees of success (Allan, 2006;Boulton, 2010;Kaur & Hegelheimer, 2005;Lee & Liou, 2003;Sun & Wang, 2003;Yoon & Jo, 2014). Further studies have also looked at how NLP influences the acquisition of the different language skills (Granger et al, 2007;Harbusch, Itsova, Koch, & K€ uhner, 2013;Meurers, 2015;Nagata, 2013;Sato, Matsunuma, & Suzuki, 2013). Given the potential identified in DDL and its accessibility to learners via computers, studies focusing on using language processing technologies and DDL are needed so as to gain a better understanding of how DDL could be implemented in MALL.…”
Section: Ddl and Language Processing Technologies As Open Educationalmentioning
confidence: 99%
“…Desde la perspectiva interactiva, la lectura implica comprensión, y ésta parte de la decodificación del texto (National Reading Panel, 2000), lo que en L2 se reporta como el reconocimiento del significado de las palabras halladas en el texto (Pasquarella, 2009;Sato et al, 2013). Sin embargo, la mera decodificación no es suficiente; se requiere fluidez en el proceso (Tindall y Nisbet, 2010), lo cual implica una lectura rápida, precisa y con prosodia (National Reading Panel, 2000).…”
Section: Proceso Lector En Segunda Lenguaunclassified
“…Sin embargo, la mera decodificación no es suficiente; se requiere fluidez en el proceso (Tindall y Nisbet, 2010), lo cual implica una lectura rápida, precisa y con prosodia (National Reading Panel, 2000). Tales elementos se incluyen en la lectura silenciosa en L2, mediante la recuperación de significados con velocidad y precisión (Sato et al, 2013).…”
Section: Proceso Lector En Segunda Lenguaunclassified